2020
DOI: 10.3390/app10010355
|View full text |Cite
|
Sign up to set email alerts
|

Impact Performance of a Plate Structure with Coconut-Inspired Microchannels

Abstract: Very few studies have been conducted in the past to reveal the underlying mechanism that causes the high-impact performance of coconuts as a natural composite material and a structure. The goal of this study is to understand the dominant microstructures of coconuts with respect to mechanical impact. In this study, we use a high-resolution X-ray computed tomography (CT) machine in scanning the microstructures and analyzing the patterns of microchannels in coconut shells. By using the established patterns, we mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Such results can lay the basis for transferring those properties into biomimetic technical applications [41]. Similarly, a very recent study [42] allows establishing a 3D model of the natural and structured composite material constituted by coconut, in the form of a flat structure with coconut-inspired microchannels. This new approach of numerical simulation allows understanding the crashworthiness of coconuts.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Such results can lay the basis for transferring those properties into biomimetic technical applications [41]. Similarly, a very recent study [42] allows establishing a 3D model of the natural and structured composite material constituted by coconut, in the form of a flat structure with coconut-inspired microchannels. This new approach of numerical simulation allows understanding the crashworthiness of coconuts.…”
Section: Introductionmentioning
confidence: 91%
“…Biomaterials exhibit a hierarchical structure [3,38,[41][42][43] with complex morphologies [1,3,30,38,[41][42][43], which makes it difficult to achieve complete characterization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the crashworthiness requirements for electrical vehicles is different from traditional vehicles [1] because additional safety features are required to protect the battery cells. In terms of designing for crashworthiness, a lot of work has been conducted looking into various material, shapes, sizes, and loading conditions [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Several composite sandwich designs such as inserts and foam-core hybrid composites were tested and it was found that these configurations have good energy absorption capabilities [2,6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several composite sandwich designs such as inserts and foam-core hybrid composites were tested and it was found that these configurations have good energy absorption capabilities [2,6,15,16]. In another study, coconut-inspired designs were used to enhance crashworthiness performance [3]. Composite corrugated tubes were also found to have excellent crushing behavior which corresponded to good energy absorption capabilities [5,11,12].…”
Section: Introductionmentioning
confidence: 99%